Community Cadres Roles in Larvae Monitoring for Dengue Prevention: Peran Kader Masyarakat dalam Pemantauan Larva untuk Pencegahan Demam Berdarah - Sekar Ayu Purwanti; Isnaini Rodiyah (Academia Open, 2025)
General Background: Dengue fever remains a persistent public health concern in Indonesia, particularly in densely populated urban areas where environmental conditions support mosquito breeding. Specific Background: The Surabaya municipal government initiated a community-based Larvae Monitoring Jury Program implemented by Surabaya Hebat cadres to reduce dengue transmission at the neighborhood level. Knowledge Gap: Despite widespread implementation, limited research has examined how cadre roles function operationally within this program framework. Aims: This study aims to analyze the roles of Surabaya Hebat cadres in the Larvae Monitoring Jury Program in Kutisari Indah Barat using Bintoro Tjokroamidjojo’s role theory encompassing motivator, facilitator, and mobilizer dimensions. Results: Findings show that cadres actively conduct routine inspections, community education, and environmental monitoring, contributing to preventive efforts, yet face obstacles including unclear task distribution, limited initiative, inconsistent community engagement, and uneven program acceptance across areas. Novelty: The study provides a contextualized qualitative analysis of grassroots health governance by mapping practical cadre functions to established role theory. Implications: Continuous evaluation, clearer role allocation, and strengthened community participation are necessary to ensure sustainable program implementation and improved dengue prevention outcomes. Highlights: Volunteers conducted door-to-door inspections and education activities on a regular schedule. Implementation encountered coordination problems and varying acceptance among residents. Ongoing assessment is required to sustain community-based vector control initiatives. Keywords:Dengue Prevention; Community Cadres; Larvae Monitoring; Public Health Program; Surabaya